2013
DOI: 10.1371/journal.pone.0070657
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Role of the Indigenous Microbiota in Cholesterol Gallstone Pathogenesis

Abstract: Background and AimsCholesterol gallstone disease is a complex process involving both genetic and environmental variables. No information exists regarding what role if any the indigenous gastrointestinal microbiota may play in cholesterol gallstone pathogenesis and whether variations in the microbiota can alter cholesterol gallstone prevalence rates.MethodsGenetically related substrains (BALB/cJ and BALB/cJBomTac) and (BALB/AnNTac and BALB/cByJ) of mice obtained from different vendors were compared for choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Fremont-Rahl et al found that compared to the control group, the incidence rate of cholesterol gallstones in sterile mice fed LD significantly increased. They believed that changes in gut microbiota could increase the occurrence of cholesterol gallstones by changes in gallbladder movement, local inflammation, and increases in mucin gene expression and mucin gel accumulation [22]. Our data also indicated that gallstone formation was associated with gut microbiota dysbiosis.…”
Section: Discussionsupporting
confidence: 65%
“…Fremont-Rahl et al found that compared to the control group, the incidence rate of cholesterol gallstones in sterile mice fed LD significantly increased. They believed that changes in gut microbiota could increase the occurrence of cholesterol gallstones by changes in gallbladder movement, local inflammation, and increases in mucin gene expression and mucin gel accumulation [22]. Our data also indicated that gallstone formation was associated with gut microbiota dysbiosis.…”
Section: Discussionsupporting
confidence: 65%
“…In the different conditions leading to NAFLD, one or more of the following mechanisms could predominate: (i) hepatic cholesterol oversecretion in bile as consequence of insulin resistance, 6 (ii) supersaturated bile and rapid phase transition owing to increased concentrations of mucins or other pronucleating agents, 7 (iii) gallbladder hypomotility, which frequently occurs in diabetics or patients with obesity, 8 and (iv) intestinal dysbiosis perturbing the cholehepatic bile salt (BS) circulation. 9 The article by Asai et al 10 in this issue of Gastroenterology proposes a novel and intriguing pathogenetic mechanism linking liver steatosis with gallstones. Indeed, the authors 10 propose that, in steatotic livers, hypoxia up-regulates the expression of hypoxia-inducible factor 1 alpha subunit (HIF1A), which reduces the expression of aquaporin (AQP)-8 and concentrates biliary lipids by suppressing water secretion from hepatocytes.…”
Section: Gallstones: Bad Company For the Steatotic Livermentioning
confidence: 99%
“…13 Finally, higher BS concentrations reaching the gut lumen may perturb the microbiota and, as a consequence, the enterohepatic BS circulation. 9 An emerging novel concept is that steatotic, hypoxic hepatocytes (mainly in the centrilobular zone) secrete less water in bile as a consequence of HIF1A-mediated suppression of AQPs (specifically AQP8), a family of integral membrane proteins that facilitate osmotically induced water transport through cell membranes. 14 Bile secretion is an osmotically driven secretory process resulting from the flow of water into the canalicular lumen in response to osmotic gradients created by active solute excretion.…”
Section: Gallstones: Bad Company For the Steatotic Livermentioning
confidence: 99%
“…These mice can then be utilized to study a variety of human infectious and immunological diseases (Zhang et al, 2010). Likewise, other studies have demonstrated that the microbiome plays roles in a variety of diverse diseases (Fremont-Rahl et al, 2013;Greer et al, 2013;Hansen et al, 2013;Karlsson et al, 2013;Kostic et al, 2013;Mathis and Benoist, 2012;Schwabe and Jobin, 2013). In general these rely on transplanting tissue biopsies from patients with tumors into a variety of immunodeficient mice and testing various treatment modalities to determine which treatment might be most efficacious for that patient's specific tumor (Hidalgo et al, 2011).…”
Section: Spontaneous and Induced Animal Modelsmentioning
confidence: 99%